A national survey of maternity services for women with obesity in pregnancy in the UK. (16th November 2010) - Modder, J; Fitzsimons, KJ
Abstract : Maternal obesity is one of the most commonly occurring risk factors in obstetric practice. A UK-wide survey assessed maternity service provision for women with obesity. The survey sought information on the availability of equipment and facilities, care structures, training and the use of guidelines and policies that were specific to obesity. Maternity units were also asked about their practices for obtaining and recording maternal weight, height and body mass index (BMI). A postal survey was sent to Heads of Midwifery at every maternity unit in the UK. 320 surveys were returned (overall response rate 88%, obstetric units 98%, alongside midwifery units 27%, free-standing midwifery units 96%). Maternal weight and BMI was reported to be recorded in the maternity notes in 100% and 96% of units, respectively. 16% of units most commonly obtained a self-reported weight, rather than one that was measured by a health professional. 39 units (12%) did not provide routine care for obese women; these included 6 (46%) alongside midwifery units and 33 (38%) freestanding midwifery units. Of the 281 units providing care for obese women, 124 (44%) did not have a guideline on maternal obesity. The most commonly used BMI cut-off for initiating additional services was 35 kg/m 2 . While a proportion of maternity units report that care structures and processes are in place for obese women, a number of areas for improvement have been identified. The Centre for Maternal and Child Enquiries obesity in pregnancy project will produce a number of recommendations for maternity services in the UK.